Post-COVID-19 vaccine Guillain-Barré syndrome; first reported case from Qatar - Almurtada Razok (12204854) (2021)
Introduction Guillain-Barré syndrome (GBS) is an immune-mediated peripheral neuropathy that was reported following meningococcus, polio, influenza and rabies vaccines. However, an association with the COVID-19 vaccine is yet to be established. Presentation of case We present the case of an elderly gentleman with no history of SARS-CoV-2 infection or any recent viral or bacterial illnesses who presented with GBS 20 days after the second dose of COVID-19 vaccination. The diagnosis was established based on physical examination, magnetic resonance imaging (MRI) of the spine, cerebrospinal fluid (CSF) analysis and electromyography (EMG). Discussion Due to the occurrence of GBS after certain types of infections, molecular mimicry has become widely acceptable as the underlying pathophysiology. The reported cases of GBS following vaccination further supported this theory, however proving a causal relationship between vaccines and GBS on the molecular level remains a challenge. Conclusions To the best of our knowledge this is the first reported case in the state of Qatar. It is important to mention that more research is needed to establish an association between COVID-19 vaccine and GBS. In our opinion, the benefits of COIVID-19 vaccine largely outweigh its risks. Other Information Published in: Annals of Medicine & Surgery License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.amsu.2021.102540